THE CHALLENGES OF INCLUSIVE SPECIAL EDUCATION IN REGULAR EDUCATION - Maia de Assis, Felipe (Revista Gênero e Interdisciplinaridade, 2023)
Inclusion in Brazil is still a challenge. Despite at least two decades after the consolidation of many of the rights of the disabled, a series of obstacles are still being faced for the inclusive process, both in special education and in regular education itself, to actually take place. Much progress has been made, but some obstacles still need to be overcome. The present work aims to reflect on the importance of inclusive education in Early Childhood Education and what to do about it. Among the specific objectives, talk about the legal system and the guaranteed right to inclusion; reflect on how important the inclusive process is; deal with the role of the family and the teacher’s position in this context. As a theoretical basis, several authors and some examples of successful inclusion on the subject in question were used. It is verified throughout the work that the elaboration of inclusive contents, pointing to an inclusive praxis; constituting this as a challenge to be faced by specialized institutions and also by regular schools, as a new way of rethinking and restructuring educational strategies, in addition to creating effective opportunities for students with special needs to access regular education.